Dispersion and Persistence of Trichogrammatoidea bactrae (Nagaraja) over Tuta absoluta (Meyrick), in Tomato Greenhouses - Cagnotti, Cynthia Lorena; Riquelme Virgala, María Begoña; Botto, Eduardo Norberto; Lopez, Silvia Noemi (2018)
Inundative biological control depends on the ability of natural enemies to disperse and persist in the environment. The objective was to evaluate the dispersion and persistence of Trichogrammatoidea bactrae (Nagaraja) on Tuta absoluta (Meyrick) eggs. Inundative releases of this parasitoid were performed in experimental tomato greenhouses. For vertical dispersion, leaves of the upper and middle third of plants were artificially infested with T. absoluta eggs; for horizontal dispersion, plants at increasing distances from a release point were infested. These eggs were renewed at days 2 and 4 to evaluate persistence. The amount of parasitized patches was registered. Logistic regression analysis was used. The position of the eggs in the plant did not affect the DE (discovery efficiency: proportion of parasitized patches). Time since release negatively affected the DE, while distance affected it only when plants were higher. These results could be used to adjust the release methodology of T. bactrae.